Gerakan Indonesia Tanpa Pacaran (GITP): Propaganda and Mobilization of Youths’ Social Praxis - Sulaiman, Akhmad (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2020)
Gerakan Indonesia Tanpa Pacaran (GITP), as a da’wa movement, rises because of moral panics encouragement. It is concerned that promiscuity among youths is increasingly out of control. The Movement presenting its mission through social media is opposed by many circles. Nonetheless, it develops rapidly and obtains many followers. This research is meant to answer questions: 1) why does GITP develop rapidly although it is opposed by many circles? 2) What propaganda techniques are used by GITP so that it receives many followers? 3) How does GITP mobilize youths’ social praxis? To answer these questions, I use Fairclough’s critical discourse analysis. The research concludes that the triumph of GITP is not separated from the totality of propaganda. It uses seven propaganda techniques. Mobilization of social praxis is done through three discourse functions namely ideational, identity, and relational function of discourse till it produces personal piety and militant community.